IS GENDER PARITY IMMINENT IN THE PROFESSIORATE? LESSONS FROM ONE CANADIAN UNIVERSITY - Wilson, Marnie; Gadbois, Shannon; Nichol, Kathleen (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
This article examined issues and implications associated with gender parity in the professoriate. The findings, based on the results from one Canadian institution’s most recent women’s committee report, emphasize the importance of monitoring progress toward gender parity by examining potential indicators of gender imbalances such as gender differences in applicant pools, starting rank and salary, and promotion applic‐ ation and attainment. This article addresses implications for recruitment, hiring, and formalized reporting mechanisms that can contribute to ultimately attaining gender parity in academia. Key words: post‐secondary education, faculty hiring, status of women Cet article porte sur les problèmes et les incidences liés à la parité hommes‐femmes dans le corps professoral universitaire. Les conclusions des auteures, basées sur les résultats d’un rapport récent préparé par un comité de femmes dans une université canadienne, soulignent l’importance de suivre l’évolution de la question de la parité hommes‐femmes en étudiant les indicateurs potentiels des déséquilibres en la matière, notamment les écarts entre le nombre de femmes et d’hommes dans les bassins de candidats, le salaire et le rang de départ ainsi que les demandes de promotion et leur obtention. Cet article traite notamment des procédures de communication d’information sur le recrutement et l’embauche pouvant favoriser la parité hommes‐femmes dans les universités. Mots clés : éducation postsecondaire, embauche des membres du corps professoral, statut des femmes